Analisis Wanprestasi dalam Perjanjian Pengikatan Jual Beli Tanah yang Melibatkan Ahli Waris: Studi Kasus Putusan Pengadilan Negeri Jakarta Utara Nomor 711/PDT.G/2023/PN JKT.UTR - Reza Bintang Prakosa; Haryo Luthfizildan. A; Ahmad Rais Imtiyaz (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study analyzes the legal implications of a preliminary sale and purchase agreement (PPJB) for land when the seller dies before signing the deed of sale and purchase (AJB). Through a case study of North Jakarta District Court Decision Number 711/Pdt.G/2023/PN Jkt.Utr, involving Dedi Suwasono (buyer) against the heirs of Iwan Herlambang (seller), it was found that the seller's obligations are transferred to his heirs based on inheritance law. When the heirs refuse to complete the transfer of land rights, this action is categorized as a breach of contract (cidera janji). The judge's decision affirms the principle of pacta sunt servanda, ordering the heirs to continue and complete the PPJB, as well as pay court costs. This finding highlights the interconnection between contract law, inheritance law, and land law in protecting buyers acting in good faith, and provides important insights into the continuity of contractual obligations after the death of one of the parties.